Logistic Mixed Models to Investigate Implicit and Explicit Belief Tracking - Lages, Martin; Scheel, Anne (Frontiers in Psychology, 2016)
We investigated the proposition of a two-systems Theory of Mind (ToM) in adults’ belief tracking. A sample of N=45 participants predicted the choice of one of two opponent players after observing several rounds in an animated card game. Three matches of this card game were played and initial gaze direction on target and subsequent choice predictions were recorded for each belief task and participant. We conducted logistic regressions with mixed effects on the binary data and developed Bayesian logistic mixed models to infer implicit and explicit mentalising in true belief and false belief tasks. Although logistic regressions with mixed effects predicted the data well a Bayesian logistic mixed model with latent task- and subject-specific parameters gave a better account of the data. As expected explicit choice predictions suggested a clear understanding of true and false beliefs. Surprisingly however, model parameters for initial gaze direction also indicated belief tracking. We discuss why task-specific parameters for initial gaze directions are different from choice predictions yet reflect Level 2 perspective taking.